A case of third degree hemorrhagic shock due to total subacute uterine inversion after delivery (Faculty of Medicine Universitas Indonesia, 2021)
Uterine inversion is a rare, but life-threatening obstetric emergency. We describe a case of total subacute uterine inversion in settings with limited resources. A multiparous (P4) 29-year-old woman with history of delivery assisted by a traditional birth attendant who used the fundal pressure technique 4 days before admission was referred due to postpartum hemorrhage. She had low blood pressure, tachycardia, and lethargic. A protruding mass from the vaginal introitus with active bleeding was visible. She diagnosed with third degree hemorrhagic shock due to total subacute uterine inversion. Resuscitation was initiated immediately and manual uterine repositioning was performed under general anesthesia. After two failed attempts, a laparotomy was performed to apply traction to the round ligaments and an incision on the cervical ring by using Allis clamps. The inversion was resolved. Next, subtotal hysterectomy was done to stop bleeding and infection.